2021
DOI: 10.1186/s40348-021-00119-7
|View full text |Cite
|
Sign up to set email alerts
|

A fresh look to the phenotype in mono-allelic likely pathogenic variants of the leptin and the leptin receptor gene

Abstract: Leptin (LEP) and leptin receptor (LEPR) play a major role in energy homeostasis, metabolism, and reproductive function. While effects of biallelic likely pathogenic variants (-/-) on the phenotype are well characterized, effects of mono-allelic likely pathogenic variants (wt/-) in the LEP and LEPR gene on the phenotype compared to wild-type homozygosity (wt/wt) have not been systematically investigated. We identified in our systematic review 44 animal studies (15 on Lep, 29 on Lepr) and 39 studies in humans re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 143 publications
0
5
0
Order By: Relevance
“…Generally, heterozygous variants were previously detected in unaffected individuals (5, 7). Heterozygous carries generally show lower BMI z-scores and lower body fat percentage than homozygous individuals (28). Yet, it is feasible that an additive effect of heterozygous variants may still have an impact on the carrier’s body weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, heterozygous variants were previously detected in unaffected individuals (5, 7). Heterozygous carries generally show lower BMI z-scores and lower body fat percentage than homozygous individuals (28). Yet, it is feasible that an additive effect of heterozygous variants may still have an impact on the carrier’s body weight.…”
Section: Discussionmentioning
confidence: 99%
“…The non-synonymous mutations p.Asp100Asn (rs724159998, 30), p.Asn103Lys (rs28954113, 6, 31, 32) and the frameshift mutation p.Gly133Val fs Ter15 (rs1307773933, 7) were detected in extremely obese children being homozygous carriers (5). Another study showed that BMI z-scores of carriers of homozygous LEP variants are generally higher than those of the heterozygous or wildtype individuals carrying the same variant (28).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a systematic literature review provided evidence for a higher frequency of metabolic abnormalities in LEP wt/- than in wt/wt subjects, including hypercholesterinemia, hyperinsulinemia, and hypertriglyceridemia. Animal studies demonstrated lower leptin levels in LEP wt/- compared to wt/wt animals, especially in relation to fat mass ( 23 ). Furthermore, in humans with lipodystrophies, a group of disorders that are characterized by a selective deficiency of subcutaneous adipose tissue and low circulating leptin levels, severe forms of NAFLD have been described together with other metabolic complications including insulin resistance and high triglyceride levels.…”
Section: Discussionmentioning
confidence: 99%
“…Several mutations in Leptin and LEP-R, including deletions, frameshifts and single nucleotide polymorphisms (SNPs), are associated with severe obesity and other diseases 12, 49 . Here we focus on pathogenic SNPs with no currently known effect on secretion levels and stability ( Extended Data Table 2, Extended Data Fig.…”
Section: Mainmentioning
confidence: 99%